KEKUATAN HUKUM AKTA PERDAMAIAN (ACTA VAN VERGELIJK) HASIL MEDIASI MENURUT PASAL 130 HIR (Studi Putusan No. 13/PDT.G/2013/PN.KPG) - Rizka Azzahra; Maryati Bachtiar; Ricki Musliadi (Peneliti.net, 2026)
One of the issues that often arises in an agreement is default (wanprestasi), which can result in losses for the creditor. In civil court practice, the judge generally offers settlement through reconciliation. If the parties agree, the court will issue a Settlement Deed (Akta Perdamaian) that has binding legal force, legal certainty, and executory power. This study employs a normative juridical research method using a legislative and case approach, examining Article 130 HIR and its application in Decision Number 13/PDT.G/2013/PN.KPG. The analysis concludes that the settlement deed, which should have served to finally and bindingly end the dispute, actually gave rise to new legal problems due to alleged breach, prompting the plaintiff to file a new lawsuit that proceeded through cassation. This situation reveals a discrepancy between the legal position of the settlement deed as a final, enforceable decision and the practice of courts accepting new lawsuits, thereby creating legal uncertainty. The appropriate legal remedy when a party breaches a settlement deed is the execution mechanism, not a new civil lawsuit..